Diseño de un sistema de climatización y ventilación para la tienda paris mall aventura plaza Trujillo - Alcántara Calderón, Daniel (2018)
The present test, the objective of describing the thermal calculations of the installations of the air conditioning systems for the PARIS MALL AVENTURA PLAZA TRUJILLO, located in the city of Trujillo, department of La Libertad, Peru. The calculations were carried out using Carrier's Hourly Analysis Program 4.60 thermal calculation software, which takes as input parameters the following: ambient temperatures, terrestrial situation, orientation of the architecture, equipment loads, lighting, capacity, type of materiality of ceilings, walls among other parameters. The sales rooms of the Paris MAP Trujillo are acclimatized through a system of compact units (Roof Top), distributed in an appropriate way to counteract the burden of the environment. For the back room area, offices, dining room, they are acclimatised by Split type direct expansion equipment. For the electrical room and board room, forced extraction is used by ventilating equipment and thus counteract with the thermal load of the same. Finally, for the systems room, air conditioning systems of the single cold-split type of direct expansion were conditioned. The air conditioning equipment is manufactured in accordance with the ARI Standard 590 (USA) construction standards according to ASHRAE 15 and assembled according to recommendations given by the manufacturer, in the location and position indicated in the plans on the platforms to be provided the work on the roof of the building.